2009
DOI: 10.1016/j.biocel.2009.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Junctin and triadin each activate skeletal ryanodine receptors but junctin alone mediates functional interactions with calsequestrin

Abstract: Summary Normal Ca2+ signalling in skeletal muscle depends on the membrane associated proteins triadin and junctin and their ability to mediate functional interactions between the Ca2+ binding protein calsequestrin and the type 1 ryanodine receptor in the lumen of the sarcoplasmic reticulum. This important mechanism conserves intracellular Ca2+ stores, but is poorly understood. Triadin and junctin share similar structures and are lumped together in models of interactions between skeletal muscle calsequestrin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 63 publications
2
91
1
Order By: Relevance
“…Phosphorylated calsequestrin strongly interacts with junctin and hence inhibits the RyR1 channel (Beard et al 2008). Junctin, but not triadin, is required for skeletal calsequestrin to exert regulatory control over RyR1 channels (Wei et al 2009a). At resting SR Ca 2þ levels, skeletal calsequestrin inhibits RyR1; by contrast, cardiac calsequestrin activates both RyR1 and RyR2 (Wei et al 2009b).…”
Section: Erp72 a Pdi-like Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated calsequestrin strongly interacts with junctin and hence inhibits the RyR1 channel (Beard et al 2008). Junctin, but not triadin, is required for skeletal calsequestrin to exert regulatory control over RyR1 channels (Wei et al 2009a). At resting SR Ca 2þ levels, skeletal calsequestrin inhibits RyR1; by contrast, cardiac calsequestrin activates both RyR1 and RyR2 (Wei et al 2009b).…”
Section: Erp72 a Pdi-like Proteinmentioning
confidence: 99%
“…These interactions are thought to be mediated by the transmembrane proteins junctin and triadin, though recent results suggest that only junctin may be crucial for the regulation of RyR proteins by calsequestrin in skeletal muscle (Wei et al 2009a). Interactions between calsequestrin and the RyR depend on the luminal Ca 2þ concentration ).…”
Section: Erp72 a Pdi-like Proteinmentioning
confidence: 99%
“…4 below and Wei et al, 2009a). The rationale was that if endogenous junctin was bound to native RyRs, then exogenous FLjun added to the luminal solution could not bind to or activate the channels.…”
Section: Resultsmentioning
confidence: 95%
“…It has been suggested that junctin may be the main protein mediator between CSQ and RyR [64]. Knockdown of junctin in myotubes reduces both depolarization-induced SR Ca 2+ release and the content of Ca 2+ in the SR [61], possibly by disrupting the signaling complex between CSQ and RyR.…”
Section: Reviewmentioning
confidence: 99%